Legal Protection for Workers Experiencing Inter-Legal Entity Transfers within Corporate Groups in Indonesia - Ratih Wedhasari; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The development of corporate groups in Indonesia has led to increasingly complex employment relations, particularly regarding the practice of transferring workers between legally distinct entities within the same corporate group. Although such transfers are economically justified by integrated business operations and centralized management, Indonesian labor law has not explicitly regulated inter–legal entity transfers. Existing regulations under the Manpower Law and the Job Creation Law primarily recognize transfers within a single legal entity as a managerial prerogative, leaving a normative gap that creates legal uncertainty and potential violations of workers’ rights. This condition is reflected in judicial practice, notably in Industrial Relations Court Decision No. 10/Pdt.Sus-PHI/2021/PN Tjk, which emphasizes formal legality while offering limited substantive protection to workers. This research employs a normative juridical method with a statutory, conceptual, and case approach. Primary legal materials include labor and corporate legislation, judicial decisions, and collective labor agreements, while secondary materials consist of legal doctrines and scholarly works. Legal materials are analyzed qualitatively through systematic interpretation to assess the adequacy of existing regulations and judicial reasoning. The findings reveal that the absence of explicit legal norms governing inter–legal entity transfers within corporate groups has resulted in inconsistent practices and weakened worker protection. Transfers are often treated as managerial policies without sufficient assessment of good faith, proportionality, or the continuity of workers’ rights. The study argues that legal protection for transferred workers should be constructed on a balanced integration of justice, legal certainty, and utility. It further proposes a dual protection model: preventive protection through explicit statutory regulation and strengthened cross-entity collective labor agreements, and repressive protection through progressive judicial interpretation and effective dispute resolution mechanisms. This study concludes that recognizing corporate groups as single economic units with labor law relevance is essential to ensure substantive justice, protect workers’ rights, and promote sustainable industrial relations in Indonesia.